Information and guidance for adults returning to higher education in Hong Kong: a case study - Kwok, Ka Yin (2009)
All investors aim at maximizing the returns on their investment. Many individuals in the workforce invest in themselves by the pursuit of further studies on a part-time basis in order to better equip themselves, face the challenges ahead and map out a brighter career path. Yet, they may make their educational decisions without adequate data and support, which leads to a less-than-optimal choice. They sometimes overestimate the potential of salary increase and career advancement upon finishing the programme. This research is undertaken to examine how individual people in the Hong Kong workforce seek information to make their decisions for their part-time education programmes.